Nurses' practices in stroke-related dysphagia in low- and middle-income countries - Kirsten Rowe; Maria N. Du Toit; Sarveshvari B. Pillay; Esedra Krüger (AOSIS, 2024)
Background: Nurses are often required to perform dysphagia screening prior to oral intake by people following stroke. Previous studies report limited knowledge of nurses in identifying symptoms of post-stroke dysphagia. Objective: To explore existing literature regarding nurses' practices and knowledge in the identification and management of post-stroke oropharyngeal dysphagia (OPD) in low- and middle income countries (LMICs). Method: A scoping review was conducted according to the PRISMA-ScR guidelines. Studies were retrieved from PubMed, Scopus, EBSCOhost (CINAHL and Health source: Nursing and Academic edition), Web of Science Core collection, and Cochrane libraries. No time frame was applied, and all included studies were screened according to predefined eligibility criteria. Results: Eight studies were included from 1 792 initial hits. Studies described nursing practices in acute care pertaining to identification and management of stroke-related dysphagia in LMICs. Increased knowledge was reported in nurses who had greater clinical experience in managing patients with dysphagia. Needs for training relating to dysphagia management and opportunities for interprofessional collaboration with speech-language therapists (SLTs) were identified. Contextual barriers specific to LMICs impacting on optimal nursing management of dysphagia included heavy workloads, staff-shortages and time constraints. Conclusion and contribution: Eight studies described nurses' practices and identified needs for the improvement of nurses' dysphagia care in LMICs. This scoping review highlighted the urgency for further research in dysphagia management that provides creative, contextually relevant solutions for improved protocols and training of health care professionals. Findings may be valuable for the multidisciplinary team involved in post-stroke dysphagia care.